O retrato da mulher negra oitocentista através do romance “Hortência” (1888): entre o passado e o presente - SILVA, Maurinea Albuquerque Ribeiro da (2024)
This article aims to analyze the literary work "Hortência" (1888) by João Marques de Carvalho (1866-1910), an author from Pará who belonged to the naturalist literary school. The book in question is used as a historical source for a study that approaches gender from two different perspectives. The first deals with intersectionality, a concept created by Kimberlé Crenshaw in 1989 to highlight the interconnection between race and gender. The second perspective deals with the notion of long duration, with Fernand Braudel as the main reference for this discussion. For Braudel, the long duration represents the union of events that intertwine regardless of their difficulty or time period. Therefore, the main objective of this article is to analyze the work "Hortência" in order to understand how Marques de Carvalho describes women in the 19th century, specifically black women. The proposal is to examine whether the author's vision and the various ways in which he portrays this woman during the events narrated in the book reflect contemporary society. The aim is to understand whether society today still sees these women in the same way or whether there have been changes over time.